2021
DOI: 10.1111/ejn.15345
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation of adolescent male rats increases anxiety and K+‐induced dopamine release in the nucleus accumbens: Role of CRF‐R1

Abstract: Early life adversity can disrupt development leading to emotional and cognitive disorders. This study investigated the effects of social isolation after weaning on anxiety, body weight and locomotion, and on extracellular dopamine (DA) and glutamate (GLU) in the nucleus accumbens (NAc) and their modulation by corticotropin releasing factor receptor 1. On the day of weaning, male rats were housed singly or in groups for 10 consecutive days. Anxiety‐like behaviors were assessed by an elevated plus maze (EPM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 92 publications
(138 reference statements)
2
20
0
Order By: Relevance
“…Regarding dopamine, post-weaning social isolation stress in rodents did not alter basal extracellular dopamine levels; however, dopamine concentrations in the nucleus accumbens were increased by a depolarizing stimulus, and the effect was stronger in rodents exposed to social isolation [ 50 ]. In comparison in humans, using psychostimulants to elicit dopamine release revealed increased striatal dopamine levels among in subjects with schizophrenia at onset of illness, independent of previous neuroleptic medication [ 51 ].…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…Regarding dopamine, post-weaning social isolation stress in rodents did not alter basal extracellular dopamine levels; however, dopamine concentrations in the nucleus accumbens were increased by a depolarizing stimulus, and the effect was stronger in rodents exposed to social isolation [ 50 ]. In comparison in humans, using psychostimulants to elicit dopamine release revealed increased striatal dopamine levels among in subjects with schizophrenia at onset of illness, independent of previous neuroleptic medication [ 51 ].…”
Section: Animal Models Of Social Isolation Distressmentioning
confidence: 99%
“…Despite some attempts to standardize the separation times, the behavioral results of this manipulation vary considerably. Several studies have discussed how maternal separation has differential ↑ "Anxiety-like" and "depressive-like" behavior in rats and mice Murthy et al, 2019Hill et al, 2018Mejía-Chávez et al, 2021Laham et al, 2022Wei et al, 2021Matsumoto et al, 2017Novoa et al, 2021 Mixed -scarcity and abuse (LBN) AMY Striatum ACC ↑"Depressive-like behavior" in rats and mice Raineki et al, 2012Wendel et al, 2021Holschneider et al, 2016 Multiple hitschronic unpredictable stress, chronic social defeat HIP PFC VTA NAc ↑ "Anxiety-like" and "depressive-like" behavior in rats and mice and Coutellier, 2018 Huang et al, 2021Saavedra et al, 2021Isgor et al, 2004Oztan et al, 2011Rodríguez-Arias et al, 2018 , Brain changes associated with behavioral changes; Brain changes without behavioral analyses. ACC, anterior cingulate cortex; AMY, amygdala; HIP, hippocampus; NAc, nucleus accumbens; PFC, prefrontal cortex; VTA, ventral tegmental area.…”
Section: Emotional and Physical Deprivationmentioning
confidence: 99%
“…Aside from depriving preweaning pups of maternal contact, additional studies have examined deprivation in adolescence by using models of social isolation housing after weaning. These studies have shown that social isolation reduces stress coping, social interaction, and reward seeking, behaviors that may reflect “depressive-like” and “anxiety-like” phenotypes ( Chang et al, 2015 ; Matsumoto et al, 2017 ; Novoa et al, 2021 ; Potrebić et al, 2021 ).…”
Section: Emotional and Physical Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine release into the NAc is a measure of both dopaminergic cell function and responsiveness and SI-R has been shown to affect dopamine release, reuptake and metabolism in reward-associated regions in a region-specific manner [Figure 3; (50)]. With regard to the NAc, SI-R has no effect on extracellular dopamine levels at baseline (89,(108)(109)(110)(111)(112), but increases basal dopamine turnover (110,112), suggesting that SI-R alters baseline dopamine release and uptake mechanisms at least in males.…”
Section: Adolescent Social Isolation and Dysregulation Of Dopamine Signaling Within The Nacmentioning
confidence: 99%